No Decrease in Blood Pressure After an Acute Bout of Intermittent Hyperpnea and Hypoxia in Prehypertensive Elderly - Stutz, Jan; Oliveras, Ruben; Eiholzer, Remo; Spengler, Christina M. (Frontiers in Physiology, 2020)
Prevalence of hypertension, subjective sleep complaints and snoring increases with age. Worse sleep and snoring, in turn, are independent risk factors to develop hypertension. Both respiratory muscle training (RMT) and intermittent hypoxia (IH) are suggested to have positive effects on these physiological and behavioral variables. This study therefore aimed to test the acute effects of a single bout of RMT, with and without IH, on resting blood pressure (BP) and sleep. Fourteen prehypertensive elderly performed a 60-min session of (a) intermittent voluntary normocapnic hyperpnea (HYP) alone, (b) HYP in combination with IH (HYP&IH) and (c) a sham intervention in randomized order. BP, hemodynamics, heart rate variability (HRV), cardiac baroreflex sensitivity (BRS) and pulse wave velocity (PWV) were assessed before and 15, 30 and 45 min after each intervention. Variables of sleep were assessed with actigraphy, pulse oximetry and with questionnaires during and after the night following each intervention. Neither HYP nor HYP&IH resulted in a decrease in BP. Repeated measures ANOVA revealed no significant interaction effect for systolic BP (p = 0.090), diastolic BP (p = 0.151), HRV parameters, BRS and PWV (all p > 0.095). Fragmentation index was lower after both HYP (−6.5 units) and HYP&IH (−8.4 units) compared to sham, p(ANOVA) = 0.046, although pairwise comparisons reveal no significant differences. There were no other significant effects for the remaining sleep variables. We conclude that one bout of intermittent hyperpnea, alone or in combination with IH, is not effective in lowering blood pressure or improving sleep in prehypertensive elderly.